Web data mining on XML documents - Wen, Yi. (2008)
The World Wide Web has become the largest and most convenient source of information. Searching and using Web data is becoming an important part in people's work and daily life. The need for collecting, extracting and analyzing information from the WWW is increasing. However, data existing on the Web is unstructured. The lack of structures in Web documents render traditional database techniques inapplicable for managing Web data. The advent of the extensible Markup Language(XML) has enabled flexible structuring of Web data. An XML document uses meaningful tags to provide semantic information for different parts of the document. An XML document is valid when it has a Document Type Definition(DTD) to describe its schema. An important issue for Web data mining is efficiently extracting data from Web documents and organize it into a proper form for data mining. Our work aims at extracting and transforming the Web data into a proper form such that they can be analyzed in a similar way as data mining in relational databases.